Non-speech input and speech recognition for real-time control of computer games - Sporka, Adam J; Kurniawan, Sri H; Mahmud, Murni; Slavik, Pavel (2006)
This paper reports a comparison of user performance (time and accuracy) when controlling a popular arcade game of Tetris using speech recognition or non-speech (humming) input techniques. The preliminary qualitative study with seven participants shows that users were able to control the game using both methods but required more training and feedback for the humming control. The revised interface, which implemented these requirements, was positively responded by users. The quantitative test with 12 other participants shows that humming excelled in both time and accuracy, especially over longer distance and advanced difficulty levels.